Relationship of nutrient content in the leaves and the effect of different pesticide usage of smallholders towards oryctes rhinoceros and its natural enemies in oil palm / Fathul Nabila Abd Karim - Abd Karim, Fathul Nabila (2019)
A field study was carried out at Tangkak,Johore for ten months starting from January until October 2017. This study is meant to examine the relationship of different insecticides usages and leaves nutrient content with the presences of Oryctes rhinoceros in the oil palm areas. Three treatments with four replications were applied. The treatments for insecticides usages are Cypermethrin, Carbofuran and one acted as a control which was untreated. Twelve smallholders with three different insecticides usage had been chosen and twelve samples had been taken as replications.As in determining the leaves nutrient content, 7th or 9th fronds were used and were brought back to the laboratory for further analysis using Dry Ashing method. The results revealed that insecticides showed a highly significant effect towards the presence of Oryctes rhinoceros. The least presence of Oryctes rhinoceros was detected at untreated area with total mean of 0.21, followed by Carbofuran with total mean of 2.63 and Cypermethrin with 3.12. This study also indicated that these insecticides had no significant effect towards three natural enemies found in oil palm area in Tangkak which were Playtymeris laevicollis, Harpalus caliginosus and Pherosophus jessoensis. Not only that, these three natural enemies also showed no relationship with the presences of Oryctes rhinoceros. As for the relationship between leaves nutrient content with the Oryctes rhinoceros presences in the oil palm, Phosphorus (P) and Magnesium (Mg) showed a positive relationship with the Oryctes rhinoceros presences while Potassium (K) and Calcium (Ca) showed a negative relationship. In addition, Zinc (Zn) and Copper (Cu) showed no relationship with the Oryctes rhinoceros presences in the oil palm. Asa conclusion, this study suggested that Oryctes rhinoceros might develop resistance to the Cypermetrin and Carbofuran insecticides. Moreover, this study also suggested that over-insecticides usages by the growers had killed the natural enemies as low presence of natural have been recorded during ten months of sampling time. In addition, ineffective environment that did not support the enhancement of the natural enemies also might be the reason of low presence of these natural enemies in the sampling areas. As for the leaves nutrient content, it is proved that these nutrients did give effect towards the presence or Oryctes rhinoceros in the field, thus as study should be further to fully acknowledge on this factor.